Depolymerization of alkaline lignin over mesoporous KF/γ-Al2O3. (14th August 2020) - Guan, Yinshuang; Zhao, Wei; Liu, Kaishuai; Guo, Tiantian; Wang, Dingkai; Cui, Mingyu; Fu, Shuiyuan; Fan, Xing; Wei, Xianyong
Abstract : A KF/ γ -Al2 O3 catalyst is prepared and used in lignin depolymerization into low-molecular weight compounds, such as phenols and aliphatic compounds. Abstract : As a kind of biomass resource, lignin is the only natural renewable resource that can provide abundant aromatic compounds, which is undoubtedly considered as the best candidate to produce value-added chemicals by lignin depolymerization. Thus, it is of great significance to develop approaches that are able to accommodate the complex structure of lignin. Herein, an efficient depolymerization method is implemented in methanol using a mesoporous solid superbase KF/ γ -Al2 O3 catalyst. Research shows that the depolymerization of lignin is not obvious below the critical temperature of methanol, and the conversion of lignin increases significantly above the critical temperature, which can reach 60.6% at 270 °C. Phenols and methoxy-substituted monocyclic aromatic compounds are predominant in the liquid products acquired by gas chromatography/mass spectrometry. Furthermore, oligomers were analyzed by time-of-flight mass spectrometry equipped with electrospray ionization. It is found that the molecular mass of the oligomers varied between 200 and 600 Da, the degree of unsaturation is mainly 4 and 8 with 1–2 aromatic rings, and the carbon number is found to be within the range of 15–30. It is speculated that the oligomers are mainly monophenyl or biphenyl compounds containing branched chains.